SKRINING BAKTERI ENDOFIT PENGHASIL AMILASE, LIPASE DAN PROTEASE DARI DAUN Syzygium myrtifolium - Rahmaniah, Rahmaniah; Astuti, Winni; Ruga, Ritbey (JURNAL ATOMIK, 2022)
Endophytic bacteria are microorganisms that throughout or part of their life cycle inside plants and will not appear certain symptoms on the plant itself. Endophytic bacteria can produce enzymes. Enzymes produced by bacterial endophytes are more beneficial because the production time is faster. One of the plants that contain bacteria is Pucuk Merah (Syzygium myrtifolium). This study aims to isolate endophytic bacteria from leaves of Pucuk Merah (Syzygium myrtifolium) and to screen these endophytic bacteria as amylase, lipase and protease producers. The results of this study were obtained there are 24 isolates of endophytic bacteria from Pucuk Merah leaves. A total of 19 bacterial isolates from 24 bacterial isolates produce amylase, 1 isolate produce lipase and 24 isolates produce protease. Keywords: Endophytic bacteria, Syzygium myrtifolium, Amylase, Lipase, Protease